2015
DOI: 10.1002/jcp.24952
|View full text |Cite
|
Sign up to set email alerts
|

TSH/TSHR Signaling Suppresses Fatty Acid Synthase (FASN) Expression in Adipocytes

Abstract: TSH/TSHR signaling plays a role in the regulation of lipid metabolism in adipocytes. However, the precise mechanisms are not known. In the present study, we determined the effect of TSH on fatty acid synthase (FASN) expression, and explored the underlying mechanisms. In vitro, TSH reduced FASN expression in both mRNA and protein levels in mature adipocytes and was accompanied by protein kinase A (PKA) activation, cAMP-response element binding protein (CREB) phosphorylation, as well as extracellular signal-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Since TSHR is detected in preadipocytes and adipocytes, 58, 59 and was shown to participate in adipogenesis, 60 disruption in this gene was already associated with body weight and energy consumption problems. 61 Chen et al 62 demonstrated that increased TSHR inhibits FASN (fatty acid synthase) expression or energy storage in mature adipocytes, showing that impairments in TSH/TSHR signaling could participate in the development of obesity. In the same way, the DGKG (Diacylglycerol Kinase Gamma) gene, that had been associated with chronic stress 63 and obesity, 64 was found upregulated in AN-neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Since TSHR is detected in preadipocytes and adipocytes, 58, 59 and was shown to participate in adipogenesis, 60 disruption in this gene was already associated with body weight and energy consumption problems. 61 Chen et al 62 demonstrated that increased TSHR inhibits FASN (fatty acid synthase) expression or energy storage in mature adipocytes, showing that impairments in TSH/TSHR signaling could participate in the development of obesity. In the same way, the DGKG (Diacylglycerol Kinase Gamma) gene, that had been associated with chronic stress 63 and obesity, 64 was found upregulated in AN-neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that HUVECs can express TSHR, which is a g -protein-coupled cell surface protein receptor [ 35 , 36 ]. The TSHR signaling pathway is not only activated in thyroid epithelium, but is also functional in other cells, such as aorta cells [ 14 ], adipocytes [ 37 ], HUVECs [ 15 ], and fibrocytes [ 36 ]. It activates cAMP and the phosphoinositide 3-kinase (PI3K) pathway [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fasn is a fatty-acid synthase, which may target endothelial nitric-oxide synthase (eNOS) in the plasma membrane by adding palmitate to eNOS; in this scenario, eNOS could generate NO in vascular tissue, and, in its absence, NO could decrease vasodilatation effectively leading to limb/nerve ischemia and macroangiopathy in T2DM [29]. Prkar2a is known to be a key upstream regulatory factor for Fasn [30, 32]. Three proteins (Gnas, Myh11, and Myh6) were found to be involved in vascular smooth muscle contraction, which is associated with vascular ischemia and poor local blood flow in macroangiopathy in T2DM [24].…”
Section: Discussionmentioning
confidence: 99%